Effect of providing information to the patient about upper gastrointestinal endoscopy on the patient’s perception, compliance and anxiety level associated with the procedure - Seda Pehlivan; Nimet OVAYOLU; Mehmet KORUK; Yavuz PEHLİVAN and Özlem OVAYOLU and Murat Taner Gülşen (Turkish Journal of Gastroenterology, 2019)
-